STUDI KUALITAS DAN PENETAPAN DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI BATANG KURANJI (JURNAL SPASIAL, 2014)
Pollution of water will have an impact on the ecological aspects, social, cultural and economical too. Thus the effort necessary improvements and countermeasures against polluted river costly when compared with the benefits derived from the river. One of the environmental problems that arise in the city of Padang was pollution in some rivers. This causes a decrease in the quality of river water, while known to the river is a source of water that is still used by people who live along the river flow. But on the other side of the river is one of the shelters of waste water or waste originating from a variety of activities such as residential population, household industry and market. Padang city, there are several rivers flowing along the residential areas in between Sungai Batang Arau, Batang Kandis, Batang Kuranji and others. Therefore, the quality of the river should be maintained so communities along the river can exploit. Capacity calculation is done on the river Batang Kuranji divided by five (5) sections calculations. These considerations are based on the same type of pollutant sources resulting in decreased water quality Kuranji Batang River, their tributaries were in and out of Sungai Batang Kuranji.Keywords: Quality, Capacity, Pollution